2015
DOI: 10.1097/wnr.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Reward positivity is elicited by monetary reward in the absence of response choice

Abstract: The neural response to positive and negative feedback differs in their event-related potentials. Most often this difference is interpreted as the result of a negative voltage deflection after negative feedback. This deflection has been referred to as the feedback-related negativity component. The reinforcement learning model of the feedback-related negativity establishes that this component reflects an error monitoring process aimed to increase behavior adjustment progressively. However, a recent proposal sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We also hypothesized that the centroparietal effect might correspond to the P3b component (Friedman et al., 1993; Luck & Kappenman, 2012; Polich, 2007). Other ERP components that have been related to associative learning, such as the P2 (Luque et al., 2015; Wills et al., 2007) or the S‐locked FRN (Holroyd et al., 2011; Varona‐Moya et al., 2015), did not yield any significant effects. In summary, Luque et al.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also hypothesized that the centroparietal effect might correspond to the P3b component (Friedman et al., 1993; Luck & Kappenman, 2012; Polich, 2007). Other ERP components that have been related to associative learning, such as the P2 (Luque et al., 2015; Wills et al., 2007) or the S‐locked FRN (Holroyd et al., 2011; Varona‐Moya et al., 2015), did not yield any significant effects. In summary, Luque et al.…”
Section: Introductionmentioning
confidence: 94%
“…We also hypothesized that the centroparietal effect might correspond to the P3b component (Friedman et al, 1993;Luck & Kappenman, 2012;Polich, 2007). Other ERP components that have been related to associative learning, such as the P2 (Luque et al, 2015;Wills et al, 2007) or the S-locked FRN (Holroyd et al, 2011;Varona-Moya et al, 2015), did not yield any significant effects. In summary, Luque et al (2017) showed that the high-value S was prioritized relatively soon after its presentation on the screen (i.e., the P1 effect), and this prioritization was insensitive to the instructed devaluation of the O (i.e., it was "habit-like").…”
Section: Introductionmentioning
confidence: 96%
“…As outlined in the introduction, the finding that the RewP is sensitive to a binary assessment of outcome valence is very robust, and has been replicated numerous times in a wide array of reward-processing tasks, as well with meta-analysis and in larger samples (Proudfit, 2015;Sambrook & Goslin, 2015;Williams et al, 2021). A number of studies have reported that the RewP appears to be sensitive only to positively valanced outcomes, and displays little to no distinction between neutral and negative outcomes (Hajcak et al, 2006;Holroyd et al, 2006;Kujawa et al, 2013;Varona-Moya et al, 2015). If so, these findings suggest that LDWs are experienced as a positive outcome, on average, despite being a net loss.…”
Section: Discussionmentioning
confidence: 88%
“…As outlined in the introduction, the finding that the RewP is sensitive to a binary assessment of outcome valence is very robust and has been replicated numerous times in a wide array of reward‐processing tasks, as well as with meta‐analysis and in larger samples (Proudfit, 2015; Sambrook & Goslin, 2015; Williams et al., 2021). A number of studies have reported that the RewP appears to be sensitive only to positively valanced outcomes and displays little to no distinction between neutral and negative outcomes (Hajcak et al., 2006; Holroyd et al., 2006; Kujawa et al., 2013; Varona‐Moya et al., 2015). If this is the case, these findings suggest that LDWs are experienced as a positive outcome, on average, despite being a net loss.…”
Section: Discussionmentioning
confidence: 99%